The research of the maximum wind speed in Tomsk and calculations of dynamic load on antenna systems; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Belan B.; Belan S.; Romanovskiy O.; Girshtein A.; Yanovich A.; Baydali S. A. Sergey Anatolievich; Terekhov S. A. Sergey Aleksandrovich (2017, 2017)
Title screen